2011
DOI: 10.1063/1.3622649
|View full text |Cite
|
Sign up to set email alerts
|

Effective reduction of fixed charge densities in germanium based metal-oxide-semiconductor devices

Abstract: Side-gate effects on the direct current and radio frequency characteristics of AlGaN/GaN high-electron-mobility transistor on Si Appl. Phys. Lett. 99, 163505 (2011) Temperature dependence of current density and admittance in metal-insulator-semiconductor junctions with molecular insulator J. Appl. Phys. 110, 083708 (2011) Synthesis and electrical and magnetic properties of Mn-doped SnO2 nanowires J. Appl. Phys. 110, 083907 (2011) Effect of the Ti molar ratio on the electrical characteristics of titanium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 21 publications
(21 reference statements)
0
20
0
Order By: Relevance
“…The use of different oxidizing atmospheres was shown to have beneficial effects on the electrical properties of dielectric/Ge structures amending electrically active defects. Such treatments include the use of wet N 2 , 15 high pressure water treatment using supercritical fluids, 16 post metal annealing in an oxygen/nitrogen mixture, 17 and high pressure (70 atm) O 2 . 18 The observed improvements may be due to the suppression of GeO desorption and to modifications of the original dielectric layer.…”
mentioning
confidence: 99%
“…The use of different oxidizing atmospheres was shown to have beneficial effects on the electrical properties of dielectric/Ge structures amending electrically active defects. Such treatments include the use of wet N 2 , 15 high pressure water treatment using supercritical fluids, 16 post metal annealing in an oxygen/nitrogen mixture, 17 and high pressure (70 atm) O 2 . 18 The observed improvements may be due to the suppression of GeO desorption and to modifications of the original dielectric layer.…”
mentioning
confidence: 99%
“…Considering the work functions for Al (4.16 eV), NiGe (5.2 eV), Ge (4.33 eV), and SiGe (4.55 eV) and the gate oxide thickness of 3-4 nm, our experimental observations of negative Vfb suggest estimated positive fixed charge densities of ~5 × 10 11 cm −2 at interfaces of SiO2/SiGe and SiO2/Ge dot. It is interesting to note that the positive fixed charges measured for our NiGe/SiO2/SiGe and Al/SiO2/Ge-dot/SiO2/SiGe MOS capacitors are in contrast to the conventional expectation of negative fixed charges produced by the thermal oxidation of SiGe alloys (LeGoues et al, 1989;Nayak et al, 1990Nayak et al, , 1992 or at high-k dielectric/Ge interfaces generated either by chemical vapor deposition or atomic layer deposition (Bai et al, 2005;Zhang et al, 2006;Deng et al, 2011) As described in our previous reports (Kuo et al, 2012;Lai et al, 2015), the interfacial SiO2 layer between the Ge dot and the SiGe shell is formed by the thermal oxidation of Si interstitials that are released from the Si substrate. The oxide layer between the Ge dot and the deposited Al gate is formed by the thermal oxidation of Si interstitials that migrate along the surface of Ge dot to its distal end.…”
Section: Discussionmentioning
confidence: 67%
“…It can be found that flat band voltage ( V fb ) values of HfO 2 /SiO 2 /Ge before and after PDA are 0.42 and 0.27 V, respectively. The calculated ideal V fb value is 0.55 V. The slightly negative V fb shift indicates positive fixed charges, which may be induced by the oxygen vacancies in the dielectrics [26, 27]. During the inert atmosphere annealing process, more oxygen vacancies may be induced, resulting in a slightly negative V fb shift.…”
Section: Resultsmentioning
confidence: 99%